[PP.37.20] THE RELATIONSHIP BETWEEN CENTRAL BLOOD PRESSURE AND LEFT VENTRICULAR MASS INDEX IN COMPARISON WITH CASUAL AND AMBULATORY BLOOD PRESSURES. (September 2016) - Shin, J.; Choi, B.Y.; Yamori, Y.; Lee, Y.; Kim, B.K.; Choi, S.Y.; Mori, M.
Abstract : Objective: Theoretically, it is postulated that the central blood pressure (BP) is more directly interact with the left ventricular mass index than casual blood pressure or ambulatory blood pressure which were measured more peripheral site. In some studies showed that central blood pressure or arterial stiffness iis more closely associated with left ventricular hypertrophy or function than others. But there is few study to compare the relationship in the general population in terms of the representative relation in healthy subjects Design and method: In the general population study for the middle aged subjects (30∼59 years) in the rural area in South Korea, 143 subjects undergone central blood pressure (BP) measurement using (HEM-9000AI: Omron Healthcare, Kyoto, Japan) and ambulatory blood pressure monitoring using TM2430, A&D in succession were analyzed. Casual blood pressure was measured six times random and alternative order using Omron 907 HEM and standard mercury sphygmomanometer. Left ventricular mass index (LVMI) was measured by echocardiography (Vivid-i, GE, USA) Results: Age was 47.9 ± 8.3 year and BMI was 25.3 ± 3.3 kg/m2. Casual systolic/diastolic BP was 123.2 ± 17.3 / 74.6 ± 12.6 mmHg by automated device (AD) and 123.2 ± 18.7/77.2 ± 11.5 mmHg by auscultation method (AM). Daytime BP was 131.5 ± 15.2/82.6 ± 9.7 mmHg and central systolic BP was 129.5 ± 19.9 mmHg. In simple and partially adjusted correlation coefficients for age sex, BMI, and 24 hour systolic BP, all of the correlation coefficients between LVMI and AD, AM, and central BPs were statistically significant. But when adjusted additionally for casual BP measured by AM, casual diastolic BPs by AD or AM and sleep systolic BP remained significant (beta = -0.15(p = 0.04), beta = -0.24 (p = 0.008), beta = -0.25(p = 0.007), respectively). But central BP or augmentation index were not independent factor for LVMI in the adjusted model (beta = -0.01, p = 0.68). And when additionally adjusted for casual systolic BP by AD, casual systolic BP by AM and nocturnal BPs remained significant. Conclusions: In terms of the relationship with LVMI, in our study done in a general population, central BP did not show additional benefit or superiority to casual or ambulatory BPs.